Gestión de inventarios y su relación con la rentabilidad de la empresa de repuestos automotriz el gato del cantón Ventanas, año 2023 - Suarez Marmolejo, Gabriela Dayana (2024)
This research project was carried out at the Automotive Parts company “El Gato” in the Ventanas Canton. Year 2023, with the aim of proposing an improvement to inventory management and thereby influencing administrative procedures, as well as increasing profitability for the company that carries out this type of activity, aimed at efficient decision-making assertive and timely type on the part of their administrators. Due to the demand of its customers, this automotive spare parts company has decided to carry out the application of a situational study, where some factors are presented that do not reflect the results in line with reality, causing a high level of merchandise, many of which do not. are necessary and therefore causes a slow return of working capital. For this reason, an inventory management model is proposed that provides reliable and immediate information so that the administrators of the Automotive Replacement Company “El Gato” can maximize their resources and profitability. The objective of this research is to determine the influence of inventory management on the profitability of the Automotive Parts company “El Gato”, in the study it was revealed that the inventory management model used is to give greater rotation to products with more demands and the strategies that have been implemented for inventory control are to meet temporary needs constantly, and that the profitability levels are favorable, however there is a very high average payment period to suppliers to improve.